2015
DOI: 10.3803/enm.2015.30.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenBsm1Polymorphism in Vitamin D Receptor Gene and Diabetic Retinopathy of Type 2 Diabetes in Korean Population

Abstract: BackgroundType 2 diabetes is one of the most common diseases with devastating complications. However, genetic susceptibility of diabetic complications has not been clarified. The vitamin D endocrine system is related with calcification and lipolysis, insulin secretion, and may be associated with many complicated disease including diabetes and cardiovascular disease. Recent studies reported that single nucleotide polymorphisms of vitamin D receptor (VDR) gene were associated with diabetic complications.MethodsI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…One abstract from conference was excluded. One article was excluded owing to lack of complete data (we tried to contact the author by email and had no response until we submitted our study) [12]. One article was excluded for departure from HWE in the control group [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One abstract from conference was excluded. One article was excluded owing to lack of complete data (we tried to contact the author by email and had no response until we submitted our study) [12]. One article was excluded for departure from HWE in the control group [13].…”
Section: Resultsmentioning
confidence: 99%
“…Although these polymorphisms had been reported to be associated with reduced steady state VDR mRNA [26], no association with risk of DR was observed in this meta-analysis. One study in Korean type 2 diabetes patients found that patients with B allele (BB or Bb) of BsmI polymorphism had significant association with lower risk of DR (severe nonproliferative DR or proliferative DR; 7.4%, 5/68) compared with patients without B allele (bb; 17.3%, 81/469; P = 0.035) [12]. However, for deficiency of complete data, this study was not included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Active vitamin D mediates its biological function by binding to vitamin D receptors. Vitamin D receptors have been found to be associated with insulin secretion and sensitivity, and have been identified in pancreatic beta cells [41]. Additionally, some genes associated with the development of diabetic retinopathy have been found, such as Bsm1 , rs2228570 , and TT .…”
Section: Discussionmentioning
confidence: 99%
“…What is more, proof of the VDR polymorphisms related with diabetic retinopathy was found. Hong et al showed that patients with the B allele (BB or Bb) of Bsm1 polymorphism in VDR were associated with lower risk of diabetic retinopathy compared to patients without the B allele (bb) in Korean type 2 diabetic patients [41]. Bucan et al showed that the bb genotype in VDR has a higher risk of developing diabetic retinopathy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al. () analysed rs1544410 in their Korean patient cohort and found an association with DR; however, the classification of retinopathy was not clear in their report.…”
Section: Chronic Hyperglycaemiamentioning
confidence: 92%